Thermo-mechanical reliability of a multi-walled carbon nanotube-incorporated solderable isotropic conductive adhesive. (February 2016) - Yim, Byung-Seung; Kim, Jong-Min
Abstract: Carbon nanotubes (CNTs) are considered as ideal candidates for the reinforcement of polymer composites due to their superior physical properties. In this paper, in order to investigate the influence of multi-walled carbon nanotubes (MWCNTs) on the reliability properties of solderable isotropic conductive adhesives (SICAs) with a low-melting-point alloy (LMPA), two types of SICAs (with 0.03 wt.% MWCNTs and without MWCNT) were formulated. Thermal shock (− 55 to 125 °C, 1000 cycles) and high-temperature and high-humidity (85 °C, 85% RH, 1000 h) tests were conducted on these samples. The SICA assemblies with and without MWCNTs showed stable electrical reliability properties during reliability testing; this stability was due to the formation of excellent metallurgical interconnection between corresponding metallization by the molten LMPA fillers. Although the mechanical pull strength of SICA assemblies decreased after thermal aging, due to the excessive layer growth and planarization of the IMCs, the SICA with MWCNTs showed enhanced mechanical reliability properties compared with the SICA samples without MWCNTs. This improvement in performance was caused by the enhancement effect of the MWCNTs. These results demonstrate that MWCNTs within SICAs can enhance the reliability properties of SICA joints due to their outstanding physical properties. Graphical abstract: Highlights: The reliability properties of MWCNT-incorporated SICAs were investigated. The metallurgically-interconnected SICAs show good electrical reliability. MWCNTs can enhance the mechanical reliability properties of SICA.